Paisagem, Espaço e Território - Alves, Andilson Francelino; Ribas, Alexandre Domingues; Candiotto, Luciano Z . P; Saquet, Marcos Aurélio; Santos, Roseli Alves dos (Formação (Online), 2012)
Na versão completa